SIMONIC: IoT Based Quarantine Monitoring System for Covid-19 - Vita Awalia Mardiana; Mochamad Mardi Martadinata; Galih Nugraha Nurkahfi; Arumjeni Mitayani; Dayat Kurniawan; Nasrullah Armi; Budi Prawara; Sudirja Sudirja; Andria Arisal; Rendra Dwi Firmansyah; Andri Fachrur Rozie; Sulaksono Priyo; Sopyan Setiana; Asih Setiarini (Jurnal Elektronika dan Telekomunikasi, 2021)
COVID-19, which has become a global pandemic since March 2020, has tremendously affected human life globally. The negative impact of COVID-19 affects societies in almost all aspects. Implementing quarantine monitoring, also social distancing, and contact tracing are a series of processes that can suppress the new infected COVID-19 cases in various countries. Prior works have proposed different monitoring systems to assist the monitoring of individuals in quarantines, as well as many methods are offered for social distancing and contact tracing. These methods focus on one function to provide a reliable system. In this paper, we propose IoT-based quarantine monitoring by implementing a geofence equipped with social distancing features to offer an integrated system that provides more benefits than one system carrying one particular function. We propose a system consisting of a low cost, low complexity, and reusable wristband design and mobile apps to support the quarantine monitoring system. For the geofencing, we propose a GPS-based geofence system that was developed by taking advantage of the convenience offered by the Traccar application. Meanwhile, we add the notification for social distancing feature with adaptive distance measurement RSSI-based set up in the android application. Based on the experiment we did to validate the system, in terms of wristband-to-smartphone communication, scanning interval in smartphone and advertising interval in wristband is best to set in 7 s for both. For social distancing notification and geofence, we measure the system performance through precision, recall, accuracy, and F-measure.